Legal Protection On The Sustainable Natural Resource Conservation Management - Anastasia Regita Rintan Sahara (Institute of Computer Science (IOCS), 2023)
This research discusses the regulations in Indonesia regarding the legal protection of sustainable natural resources conservation and the implementation of sustainable principles. This research used a statutory approach by examining the rules and laws related to the legal issues discussed. Even though the law has regulated the protection and management of sustainable natural resource conservation, the community still needs to implement the management of natural resources properly and orderly. Then, in order to protect the conservation of natural resources, it must be managed strictly and balanced to become internalized into laws and regulations Based on the description above, the results of the discussion can be concluded that Law Number 5 of 2009 has regulated the protection and management of sustainable natural resource conservation.